Palmitoylated phosphodiester gapmer designs with albumin binding capacity and maintained in vitro gene silencing activity - Cai, Yunpeng; Makarova, Anna-Marie; Wengel, Jesper; Howard, Kenneth A (The Journal of gene medicine, 2018)
BACKGROUND: Antisense gapmer oligonucleotide drugs require delivery and biodistribution enabling technologies to increase in vivo efficacy. An attractive approach is their binding and consequent transport by the endogenous human serum albumin pool as mediated by fatty acid incorporation into the gapmer design. METHODS: The present study investigated the effect of palmitoyl modification and position on albumin-binding, cellular uptake and in vitro gene silencing of gapmers with either a phosphorothioate (PS) or phosphodiester (PO) backbone. RESULTS: Two palmitoyls positioned exclusively at the 5' end, or a single palmitoyl at both the 3' and 5' positions, showed similar binding to human serum albumin as demonstrated by a gel-shift assay. Decreased cellular uptake determined by flow cytometry (27% compared to nonpalmitoyl gapmers) was observed for palmitoylated Cy5.5 labelled gapmers. However, HER3 (human epidermal growth factor receptor 3) gene silencing was exhibited by the palmitoylated gapmers with transfection agent in PC-3 and Caco-2 cells (68% and 62%, respectively), which was comparable to nonpalmitoyl gapmers (68% and 82%, respectively). Importantly, PO gapmers with a single palmitoyl positioned at both the 3' and 5' positions showed high silencing efficiencies (68% and 66% in PC-3 and Caco-2 cells, respectively) similar to those of PS nonpalmitoylated gapmers (67% and 66% in PC-3 and Caco-2 cells, respectively) in the absence of a transfection agent. CONCLUSIONS: The present study defines phosphodiester gapmer design criteria exhibiting high gene silencing activity and albumin binding that may be utilized with potentially less in vivo toxicity that can be associated with phosphorothioate gapmer designs.
Keywords: molekulární struktura; Protein Binding; Humans; lidé; Receptor, ErbB-3; lipoylace; Molecular Structure; vazba proteinů; receptor erbB-3; transfekce; Oligonucleotides, Antisense; Albumins; techniky in vitro; Transfection; antisense oligonukleotidy; Cell Line, Tumor; nádorové buněčné linie; Lipoylation; umlčování genů; Gene Silencing; albuminy; In Vitro Techniques